The Effects of Managers' Purposeful Performance Information Use on American Hospital Performance. Issue 1 (2nd January 2020) - Kim, Taehee; Johansen, Morgen; Zhu, Ling
Abstract: There is a growing body of research on the impact of purposeful performance information (PPI) use on organizational performance (Kroll, 2015a), but questions remain about how a top manager's operating context may affect the relationship between PPI use and performance. In this study, we examine the relationship between top managers' PPI use and performance, and cross-sector differences in the relationship between PPI use and performance. We test our hypotheses by combining survey data of nearly 1, 000 top managers from public, private, and nonprofit American hospitals with indirect (client satisfaction), direct (patient readmission rates), and perceptual (managers' self-assessment) performance measures, while controlling for task. We move beyond overall performance information use by exploring the relationship between PPI use and performance in four specific decision areas. We observe a fair amount of homogeneity across the three sectors but also find salient differences regarding how PPI use is linked to different performance indicators. While public hospitals primarily use PPI to meet community needs, nonprofit and for-profit hospitals use PPI to improve patient outcomes. The article concludes with a discussion of the findings within the performance management and cross-sector differences literatures.